Invariant-based reconstruction of bidimensional elasticity tensors. (1st June 2016) - Auffray, N.; Ropars, P.
Abstract: In the present paper a method to reconstruct the 2D elasticity tensor from observations is proposed. The novelty of the method, compared to other ones, is that this approach is based on the identification of the invariants, rather than the components, of the elasticity tensor. The main advantage is that all the information concerning the material, such as its symmetry class and the orientation of the tested sample, are obtained during the reconstruction process. We believe that such an approach based on intrinsic quantities may find interesting applications for the identification of mechanical parameters based on full-field measurements.